2021
DOI: 10.3390/ijms22147761
|View full text |Cite
|
Sign up to set email alerts
|

MYC Ran Up the Clock: The Complex Interplay between MYC and the Molecular Circadian Clock in Cancer

Abstract: The MYC oncoprotein and its family members N-MYC and L-MYC are known to drive a wide variety of human cancers. Emerging evidence suggests that MYC has a bi-directional relationship with the molecular clock in cancer. The molecular clock is responsible for circadian (~24 h) rhythms in most eukaryotic cells and organisms, as a mechanism to adapt to light/dark cycles. Disruption of human circadian rhythms, such as through shift work, may serve as a risk factor for cancer, but connections with oncogenic drivers su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 184 publications
(274 reference statements)
2
14
0
Order By: Relevance
“…The circadian clocks and their downstream factors are responsible for a variety of physiological and pathological functions including metabolism, aging, and immunity [24][25][26][27][28][29][30][31][32][33][34] . Interestingly, Jamison B Burchett et al found that MYC in cancer cells can disturb the molecular clock, whereas the clock disruption in cancer can promote MYC 35 . Justin P Favaro et al found that the epidermal growth factor (EGF) is critical for tumor progression in renal cancers, which can be considered as a potential drug target 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The circadian clocks and their downstream factors are responsible for a variety of physiological and pathological functions including metabolism, aging, and immunity [24][25][26][27][28][29][30][31][32][33][34] . Interestingly, Jamison B Burchett et al found that MYC in cancer cells can disturb the molecular clock, whereas the clock disruption in cancer can promote MYC 35 . Justin P Favaro et al found that the epidermal growth factor (EGF) is critical for tumor progression in renal cancers, which can be considered as a potential drug target 36 .…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the overexpressed stemness transcription factors speeding the cell cycle and forcing adaptation of its checkpoints, as discussed in Section 4 and illustrated in Figure 2 . In addition, the direct competition of the main reprogramming transcription factor, MYC/MAX, with the CLOCK/BMAL1 dimer [ 125 ] in the G1/S and G2M checkpoints [ 135 ], which can be overcome through upregulated MYC [ 136 ] (as designated on Figure 2 ), should be highlighted.…”
Section: The Circadian Clock (Cc) Paces the Mitotic Cell Cycle Ddr Ch...mentioning
confidence: 99%
“…This may be related to the overexpressed ESC transcription factors speeding the cell cycle and forcing adaptation of its checkpoints as discussed in section 4 and illustrated in Fig.2. In addition, the direct competition of the main reprogramming transcription factor, MYC/MAX, with the CLOCK/BMAL1 dimer [80] in the G1/S and G2M checkpoints [89], which can be overcome through upregulated MYC [90](as designated on Fig.2), should be highlighted.…”
Section: The Circadian Clock (Cc) Paces the Mitotic Cell Cycle Ddr Checkpoints And Reciprocally The Tert-dependent Hayflick Limit Count Imentioning
confidence: 99%
“…2. In addition, the direct competition of the main reprogramming transcription factor, MYC/MAX, with the CLOCK/BMAL1 dimer [79] in the G1/S and G2M checkpoints [89], which can be overcome through upregulated MYC [90](as designated on Fig. 2), should be highlighted.…”
Section: The Bi-phasic CC Is An Autoregulatory Transcriptional Feedba...mentioning
confidence: 99%